Identifikasi Pengaruh Jenis Air Perendaman terhadap Fase Mitosis dan Pertumbuhan Akar Bawang Merah (Allium cepa L.) dengan Menggunakan Air Biasa, Air AC, dan Air Hujan - Laura Capenesi Simanjuntak; Dhea Miranda Tambunan; Immanuel Siregar; Andrian Raja Noel Tampubolon; Larasati Arum Utami (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to determine the effect of using tap water, air conditioner (AC) water, and rainwater on root growth and mitotic phases in shallot roots (Allium cepa L.). The study employed an experimental method with a quantitative descriptive approach and a Completely Randomized Design (CRD). Shallot bulbs were immersed for 48 hours in three different types of water: tap water, AC water, and rainwater. Observations were conducted on root length and mitotic phases through microscopic examination using the squash method. Data were collected through direct observation and documentation of the observation results, then analyzed descriptively by calculating the average root length and the frequency of mitotic phases observed. The results showed that all treatments were able to support root growth and mitotic activity in the root meristem tissue of shallots. The best root growth was observed in the tap water and rainwater treatments, with an average root length of 1.8 cm, while the AC water treatment produced an average root length of 1.7 cm. Microscopic observations revealed that root cells in all treatments were predominantly in the telophase stage, characterized by the reformation of the nuclear membrane and the initiation of cytokinesis. Differences in mineral content among the water types were presumed to influence cell division activity and root cell elongation. Therefore, the type of soaking water affected root growth, although all treatments were capable of supporting the mitotic process in Allium cepa L.